KONKĖ: the first public transport in Vilnius - Vanagas, Jurgis (Transport, 2017)
The first public rail transport in the world started functioning in 1820. Like everywhere at that time, horsedrawn coaches heaved on tracks were the most popular. The first horse-drawn tram started carrying passengers in the industrial region of Wales, England. Starting from 1893, three the so called konkė lines of such a tram started operating in Vilnius. Although the ticket was expensive to the city residents of those days, however, they intensively used this kind of transport: in 1909, 2.6 million passengers were transported. Although attempts to replace horse drawn-vehicles by internal combustion engines after the First World War were made, this form of transport was found to be irrational and soon gave the way to buses. Initiative for the trams equipped with electric motors was shortly defeated in Vilnius: lack of funds was felt, and confusion in the administration of the city was predominating. For the period 1915–1920, the local government changed very frequently. In 1926, konkė tracks were dismantled. Its remains still can be seen at the enclosures of the embankment of the Vilnia (Vilnios upė) confluence. The coaches were sold for suburban residents that erected small cattle-sheds for domestic animals.First published online: 12 Apr 2016